2013
DOI: 10.1080/15402002.2011.643968
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Predictors of Sleep Dysfunction: The Role of Anxiety Sensitivity, Dysfunctional Beliefs, and Neuroticism

Abstract: The present study examined the relationship of anxiety sensitivity, dysfunctional beliefs about sleep and neuroticism on sleep disturbance. Previous research of these three related concepts-each describing a different kind of reactivity to interoceptive or environmental events-have served as predictors of insomnia and insomnia-related distress; however, it is not known how these concepts have distinctive prediction of sleep outcomes. We completed an Internet survey of 149 undergraduate student participants, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 35 publications
10
48
1
Order By: Relevance
“…This hypothesis was confirmed as expected from prior reports (Calkins et al, 2013; Duggan et al, 2014; Kajimura et al, 1998; Taylor et al, 2005). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This hypothesis was confirmed as expected from prior reports (Calkins et al, 2013; Duggan et al, 2014; Kajimura et al, 1998; Taylor et al, 2005). …”
Section: Discussionsupporting
confidence: 92%
“…For example, the Neuroticism component of the 5-factor theory of personality, as quantified using the NEO Personality Inventory Revised (NEO-PI-R) (Costa and McCrae, 1992), is a significant predictor of both the Pittsburgh Sleep Quality Index (PSQI) (Buysse et al, 1989) measure of poor sleep (Calkins et al, 2013) as well as of poor sleep hygiene (Duggan et al, 2014). Similarly a large epidemiological study (Taylor et al, 2005) has shown elevated levels of trait anxiety in persons with versus without insomnia using the Spielberger State-Trait Anxiety Index-Trait Version or STAI-T (Spielberger et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with initial hypotheses, results also revealed that AS cognitive concerns rather than AS physical concerns or AS social concerns, mediated the association between the unacceptable thoughts domain of OCD and symptoms of insomnia. Previous research has indicated distinct associations between AS cognitive concerns and the unacceptable obsessions dimension of OCD (Wheaton et al, 2012;Raines et al, 2014b) as well as symptoms of insomnia (Vincent and Walker, 2001;Calkins et al, 2013). Consistent with this research, the current findings extend the limited empirical work available establishing a link between the unacceptable thoughts domain of OCD and sleep disturbances by identifying a potential mechanism that partially accounts for this association.…”
Section: Discussionsupporting
confidence: 87%
“…Calkins, Hearon, Capozzoli, and Otto (2013) extended this research by examining the associations between AS and sleep dysfunction after accounting for two highly relevant sleep related constructs, dysfunctional beliefs about sleep and neuroticism. The authors found that whereas AS total scores did not significantly predict sleep dysfunction, the cognitive concerns subscale did.…”
Section: Introductionmentioning
confidence: 97%
“…Email: tramonti.francesco@gmail.com There is evidence that subclinical mood and anxiety symptoms play a significant role in sleep disorders. Insomnia is frequently an anticipatory symptom of mood disorders and the interdependence between subclinical anxiety and insomnia is proved by research findings, which identify neuroticism and cognitive-emotional hyperarousal as strong predictors of insomnia (Calkins, Hearon, Capozzoli, & Otto, 2013;Fernández-Mendoza et al, 2010;Spiegelhalder, Regen, Nanovska, Baglioni, & Riemann, 2013). Furthermore, relevant clinical and theoretical models emphasise the correlation between insomnia and central nervous system activation (Vgontzas et al, 2001).…”
Section: Introductionmentioning
confidence: 95%